Some aspects of Bay of Bengal cyclone of 29 January to 4 February 1987 - MANDAL, J. C.; KALSI, S. R.; VEERARAGHAVAN, K.; HALDER, S. R. (MAUSAM, 1990)
A satellite study of an unusual tropical cyclone is made to, investigate genesis, intensification, movement and the decay over sea. Dvorak technique has been applied for its Intensity analysis. Satellite cloud imagery analysis indicates that initial genesis was spawned by cross equatorial surges and mechanical subsidence occurring in the relatively cloud free area between deep layer convective cloud masses. Subsequent intensification was favoured by high sea surface temperature and suitable synoptic settings. It appears that initial movement of the vortex was guided by b-effect and subsequent movement by its environmental steering current. New convective cloud mass growth was observed in the direction of its movement and during change of its direction of movement, its speed became slow or it remained stationary for some time. Presence of dry slot in western and southwestern side in its intense stage and elongation of associated cloud mass northeastwards towards the later part of its life indicate its increasing interaction with subtropical westerly flow. This finally led to its dissipation right over sea where sea surface temperature was also relatively less.